KERAGAAN MODEL KEBIJAKAN PEMBANGUNAN EKONOMI SEKTORAL DI SUMATERA UTARA - Eko Wahyu Nugrahadi (Quantitative Economics Journal, 2013)
In macro North Sumatra province after the economic crisis shows encouraging, but it is not without problems, First, the level of income per worker are low, along with labor and a relatively large increase but its relative share of GDP declined, and the second inequality distribution of labor because they serious amount of excess agricultural labor while other sectors can not absorb it. Specifically this study aimed to analyze the variability model of sectoral economic development policy in the province of North Sumatra.The analysis in this study is based on SAM model approach. Based on the results of the analysis has identified six sectors as the leading sector in North Sumatra. Industrial eat, shop, Beverages and Tobacco is a sector that has the possibility to be developed as the most optimal model of the development of sectoral economic development policy. Food, Beverages and Tobacco is categorized as agro-industry sector. Therefore agroindustrialisasi strategy (agroindustrialization strategy) is a strategy options industrialization policies are applied in order to create a strong economy of North Sumatra in the future.